1999
DOI: 10.1007/s004050050146
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of the high jugular bulb in patients with M�ni�re's disease and pulsatile tinnitus

Abstract: The aim of this retrospective study was to evaluate the functional results of surgical lowering of the high jugular bulb in the treatment of patients with Ménière's disease and pulsatile tinnitus. Fifteen patients with disabling Ménière's disease associated with pulsatile tinnitus and a high and medial jugular bulb were included in this study. As treatment a complete mastoidectomy was performed, after which the jugular bulb was freed by an infralabyrinthine and subfacial approach. The bulb was then displaced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Pulsatile tinnitus could be explained by a transmission of the venous pulsation and/or turbulent flow to the inner ear structures [10]. As it was proposed earlier the effect on the endolymphatic duct/ sac may be direct or indirect, causing a decrease of the endolymph secretion [14]. In the present case a direct connection between jugular bulb diverticulum and endolymphatic sac was detected (Fig.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Pulsatile tinnitus could be explained by a transmission of the venous pulsation and/or turbulent flow to the inner ear structures [10]. As it was proposed earlier the effect on the endolymphatic duct/ sac may be direct or indirect, causing a decrease of the endolymph secretion [14]. In the present case a direct connection between jugular bulb diverticulum and endolymphatic sac was detected (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…The progression of the symptoms in the first case could be explained by progression of the jugular bulb diverticulum since the previous investigators suggested non-anatomically stable and progressively modeled by centrifugal hemodynamic forces medial jugular bulb [14]. In this patient the diverticulum circumvented the membranous labyrinth inferiorly what is seen on the MR image (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…The HJB is thought to be the etiology of the Meniere syndrome in these patients. These patients have undergone mastoidectomy 7,8 and the insertion of a tab of surgical wax to separate the jugular bulb from the inner ear structures. Their vertigo was cured in 92% of cases and the PT disappeared in 23% and improved in 31%.…”
Section: Discussionmentioning
confidence: 99%
“…This disturbance can be serious enough that complex transtemporal operations have been done to cure the bruit by interposing a pad of surgical wax between the dome of the jugular bulb and the SCC. 7,8 The pulsatility of the bruit could be generated by an adjacent internal carotid artery pulsating against a distended jugular bulb or more likely be the consequence of variations of the venous flow in the proximity of the heart caused by the contraction of the atrium and the opening and closing of the pulmonary valve.…”
Section: Introductionmentioning
confidence: 99%
“…A high jugular bulb can be diagnosed by CT imaging. Surgically, ligating or lowering the jugular bulb and interposing Teflon or bonewax can abolish or diminish this form of tinnitus [90,91]. Transvenous stent-assisted coil embolization has been used as well for treating this condition [92].…”
Section: High Jugular Bulbmentioning
confidence: 99%